2022
DOI: 10.1039/d2cb00113f
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical course of cobalamin-dependent radical SAM methylation by TokK and ThnK

Abstract: TokK and ThnK stereoselectively abstract the pro-S hydrogen, and methylation proceeds with inversion of absolute configuration at C6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…It was hypothesized that the three observed products (i.e., 18-P , 10-P , and 11-P ) are produced sequentially beginning with C2′-methylation of 2′-dAMP ( 3 → 18-P , Figure A). OxsB then catalyzes dehydrogenation of the C2′-CH 3 methyl to yield the methylidene 10-P rather than a second round of methylation as observed in other radical-mediated methyltransferases. Although examples of radical SAM catalyzed dehydrogenation of alcohols, thiols, and amines are well-known, biological C-CH 3 dehydrogenase activity has not been previously reported for a radical SAM enzyme. Nevertheless, NosL from nosiheptide biosynthesis catalyzes C–C desaturation of a substrate structural analogue, and DarE from the darobactin maturation pathway has been identified to catalyze off-pathway dehydrogenation of the C α –C β bond of a tryptophan residue in its peptide substrate. , Once formed, 10-P could then serve as an acceptor for OxsB catalyzed addition of the 5′-deoxyadenosyl radical ( 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was hypothesized that the three observed products (i.e., 18-P , 10-P , and 11-P ) are produced sequentially beginning with C2′-methylation of 2′-dAMP ( 3 → 18-P , Figure A). OxsB then catalyzes dehydrogenation of the C2′-CH 3 methyl to yield the methylidene 10-P rather than a second round of methylation as observed in other radical-mediated methyltransferases. Although examples of radical SAM catalyzed dehydrogenation of alcohols, thiols, and amines are well-known, biological C-CH 3 dehydrogenase activity has not been previously reported for a radical SAM enzyme. Nevertheless, NosL from nosiheptide biosynthesis catalyzes C–C desaturation of a substrate structural analogue, and DarE from the darobactin maturation pathway has been identified to catalyze off-pathway dehydrogenation of the C α –C β bond of a tryptophan residue in its peptide substrate. , Once formed, 10-P could then serve as an acceptor for OxsB catalyzed addition of the 5′-deoxyadenosyl radical ( 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, OxsB was also found to be responsible for a series of consecutive reactions beginning with C2′ methylation. In contrast to several other B 12 -dependent radical SAM enzymes, however, these reactions do not involve repeated methylation at either the same site or the newly introduced methyl substituent resulting in ethyl, iso -propyl, tert -butyl, or sec -butyl groups (Figure S2). Instead, OxsB catalyzes C–C dehydrogenation of the newly installed methyl group followed by radical addition of 5′-deoxyadenosine to the resulting methylidine moiety.…”
Section: Introductionmentioning
confidence: 90%
“…Crystal structures of Mmp10, which catalyzes C -methylation at the Cδ position of the arginine residue of methyl-coenzyme M reductase, did not elucidate the stereoselectivity of the hydrogen atom abstraction by 5′-dA· . Detailed biochemical analysis of TokK and ThnK with stereoselectively deuterated substrates revealed that inversion of configuration occurs during the TokK and ThnK reactions . In the Orf29 reaction, two molecules of SAM appear to be accommodated precisely in the active site and one molecule of SAM coordinates to the [4Fe-4S] cluster, where it is reductively cleaved to form 5′-dA· and Met ( 6 ).…”
mentioning
confidence: 99%
“…26 Detailed biochemical analysis of TokK and ThnK with stereoselectively deuterated substrates revealed that inversion of configuration occurs during the TokK and ThnK reactions. 23 In the Orf29 reaction, two molecules of SAM appear to be accommodated precisely in the active site and one molecule of SAM coordinates to the [4Fe-4S] cluster, where it is reductively cleaved to form 5′-dA• and Met (6). The generated 5′-dA• abstracts the pro-R hydrogen atom of C-4″ of another molecule of SAM to yield the substrate radical and 5′-dA (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation